Vibro-Acoustic Formulation of Elastically Restrained Shear Deformable Orthotropic Plates Using a Simple Shear Deformation Theory (Journal of Modern Mechanical Engineering and Technology, 2021)
A method is presented for vibro-acoustic analysis of elastically restrained orthotropic shear deformable plates subjected to excitation forces at different locations. The vibration of the shear deformable plate is formulated on the basis of the Ritz method and a simple first-order shear deformation theory in which 4 rather than 5 displacement components are used to simulate the deformation of the plate. The accuracy of the modal characteristics (natural frequency and mode shape) of an orthotropic plate predicted using the proposed method is verified by those obtained using other methods. The vibration responses of the plate are used in the first Rayleigh integral to construct the sound pressure level (SPL) curves of the plate subjected to excitation forces at different locations. The suitability of the present method for sound radiation analysis is validated by comparing the SPL curve obtained using the present method with those obtained using the other methods. The effects of different system parameters on the SPL curve of the plate are studied by means of several numerical examples. It has been shown that excitation location has significant effects on the smoothness of the SPL curve.